Female-Voice Song and Women’s Musical Agency in the Middle Ages
1 online resource.
Keywords: This collection of seventeen essays newly identifies contributions to musical culture made by women before 1500 across Europe. You will learn about repertoire from such diverse locations as Iceland, Spain, and Italy, and encounter examples of musicianship from the gender-fluid professional musicians at the Islamicate courts of Syria to the nuns of Barking Abbey in England. The book shows that women drove musical patronage, dissemination, composition, and performance, including within secular and ecclesiastical contexts, and also reflects on the reception of medieval women’s musical agency by both medieval poets and by modern recording artists. Contributors are David Catalunya, Lisa Colton, Helen Dell, Annemari Ferreira, Rachel Golden, Gillian L. Gower, Anna Kathryn Grau, Carissa M. Harris, Louise McInnes, Lisa Nielson, Lauren Purcell-Joiner, Megan Quinlan, Leah Stuttard, Claire Taylor Jones, Melissa Tu, Angelica Vomera, and Anne Bagnall Yardley.